Every-other-day fasting inhibits pyroptosis while regulating bile acid metabolism and activating TGR5 signaling in spinal cord injury - Song, Honghu; Pang, Rizhao; Chen, Zhixuan; Wang, Linjie; Hu, Xiaomin; Feng, Jingzhi; Wang, Wenchun; Liu, Jiancheng; Zhang, Anren (Frontiers in Molecular Neuroscience, 2024)
Every-other-day fasting (EODF) is a form of caloric restriction that alternates between periods of normal eating and fasting, aimed at preventing and treating diseases. This approach has gained widespread usage in basic research on neurological conditions, including spinal cord injury, and has demonstrated significant neuroprotective effects. Additionally, EODF is noted for its safety and feasibility, suggesting broad potential for application. This study aims to evaluate the therapeutic effects of EODF on spinal cord injury and to investigate and enhance its underlying mechanisms. Initially, the SCI rat model was utilized to evaluate the effects of EODF on pathological injury and motor function. Subsequently, considering the enhancement of metabolism through EODF, bile acid metabolism in SCI rats was analyzed using liquid chromatography-mass spectrometry (LC–MS), and the expression of the bile acid receptor TGR5 was further assessed. Ultimately, it was confirmed that EODF influences the activation of microglia and NLRP3 inflammasomes associated with the TGR5 signaling, along with the expression of downstream pyroptosis pathway related proteins and inflammatory cytokines, as evidenced by the activation of the NLRP3/Caspase-1/GSDMD pyroptosis pathway in SCI rats. The results demonstrated that EODF significantly enhanced the recovery of motor function and reduced pathological damage in SCI rats while controlling weight gain. Notably, EODF promoted the secretion of bile acid metabolites, activated TGR5, and inhibited the NLRP3/Caspase-1/GSDMD pyroptosis pathway and inflammation in these rats. In summary, EODF could mitigate secondary injury after SCI and foster functional recovery by improving metabolism, activating the TGR5 signaling and inhibiting the NLRP3 pyroptosis pathway.